Efektivitas Pemberian Jeruk Nipis Kecap Terhadap Balita ISPA di Wilayah Kerja UPTD Puskesmas Koncara Tahun 2026 - Irena Endang Widuri; Nova Rati Lova; Elma Theana (Public Health Journal, 2026)
Acute Respiratory Infection (ARI) is one of the common health problems among toddlers. Symptoms such as cough and respiratory discomfort may affect children's comfort and health status. One non-pharmacological supportive approach is the administration of lime juice combined with sweet soy sauce. This study aimed to determine the effectiveness of lime and soy sauce administration in reducing ARI symptoms among toddlers in the working area of Koncara Public Health Center in 2026. A quasi-experimental pretest-posttest design involving an intervention group and a control group was used. The sample consisted of 40 toddlers, including 20 respondents in the intervention group and 20 respondents in the control group. ARI symptoms were assessed using an observation sheet. Data were analyzed descriptively and statistically using the Shapiro-Wilk, Wilcoxon, and Mann-Whitney tests at a significance level of p